2017
DOI: 10.1111/jphd.12246
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness analysis of two caries prevention methods in the first permanent molar in children

Abstract: PFS should be the preferred method for the prevention of dental caries lesion on the occlusal surface of the first permanent molar, especially in children who are at high risk and have barriers of access to dental care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 32 publications
0
22
3
Order By: Relevance
“…The 34 articles identified correspond to 33 studies, because one study was reported in more than one article. Finally, 33 complete economic evaluations were included for data extraction and analysis …”
Section: Resultsmentioning
confidence: 99%
“…The 34 articles identified correspond to 33 studies, because one study was reported in more than one article. Finally, 33 complete economic evaluations were included for data extraction and analysis …”
Section: Resultsmentioning
confidence: 99%
“…A second study used a Markov model to simulate disease progression and cost impact over a period of 9 years. 240 Both disease progression and sealant failure probabilities were derived from the literature, and 2 scenarios were tested based on the probability of replacing a failed sealant. In the scenario where 100% of failed sealants were replaced, the incremental cost-effectiveness ratio was $156.87 per first episode of caries lesion averted.…”
Section: Sealantsmentioning
confidence: 99%
“…A second article made a similar cost comparison of pit and fissure sealants to fluoride varnish but modeled the simulated progression of caries over a 9-year period. 297 This model found that pit and fissure sealants were less expensive and more effective than fluoride varnish in preventing occlusal lesions. The incremental costeffectiveness ratio for sealants was $156.87 per first lesion averted when the assumption was made that 100% of sealants placed would require replacement at some time over the 9 years.…”
Section: Sealantsmentioning
confidence: 99%